Global Scaling Up Handwashing Project : Insights from Designing a Handwashing Station for Rural Vietnamese Households - World Bank (Washington, DC, 2012)
The Water and Sanitation Program's (WSP) Global Scaling Up Handwashing Project (HWWS) is testing an array of interventions to promote handwashing with soap among mothers and children in rural Vietnam. These interventions include mass media and interpersonal communication through organizations such as the Vietnam women's union. Of particular and growing interest is the role of handwashing stations. In a household setting, a handwashing station is a designated space bringing together water and soap to wash hands, ideally in close proximity to the latrine or the food preparation area. Handwashing stations influence individuals' chance to perform a behavior, regardless of their ability and motivation to do so. While sinks in kitchens and bathrooms are the norm in developed nations, they are not in most resource-scarce countries.